Pengaruh Kecerdasan Logika Matematika Terhadap Kemampuan Pemahaman Konsep Siswa Dalam Pembelajaran Matematika di MI Miftahul Ulum Pandanarum - Akhmad Fauzi; Yushinta Lailatul Rohmah (Academicus: Journal of Teaching and Learning, 2023)
In the context of competitive education, enhancing the quality of human resources through education is of utmost importance. The diverse intelligence of humans is widely recognized, aligning with the multiple intelligences theory proposed by Howard Gardner. However, the results of the 2018 PISA assessment reveal a low level of mathematical proficiency among Indonesian students, highlighting the urgent need to understand the factors influencing this ability. This article focuses on the role of mathematical logical intelligence as a key factor in understanding mathematical concepts. The aim of this study is to identify the influence of mathematical logical intelligence on students' understanding of mathematical concepts at MI Miftahul Ulum Pandanarum. The research method used is an associative approach with a quantitative approach, and data were collected through a questionnaire on mathematical logical intelligence and a test of conceptual understanding ability. The research sample consisted of 120 students. The data were analyzed using simple linear regression. Based on the results of this research, an R-squared value of 0.083 (83%) indicates that mathematical logical intelligence has an influence on students' understanding of concept abilities, while 17% is influenced by other variables. The t-test results reveal that the calculated t-value of 3.266 is greater than the tabulated t-value of 1.981, leading to the conclusion that there is a significant influence between the mathematical logical intelligence variable (X) and the concept comprehension ability variable (Y). With a significance value (Sig.) of 0.001 < 0.05, the alternative hypothesis  Ha is accepted, and the null hypothesis Ho is rejected.